Synthesis and disassembly of an organometallic polymer comprising redox-active Co4S4 clusters and Janus biscarbene linkers. Issue 31 (30th March 2022) - Gillen, Jonathan H.; Moore, Connor A.; Vuong, My; Shajahan, Juvairia; Anstey, Mitchell R.; Alston, Jeffrey R.; Bejger, Christopher M.
Abstract : Discrete Co4 S4 clusters can be reversibly crosslinked into redox-active frameworks using Janus bis-N-heterocyclic carbene (NHC) ligands. Abstract : Here, we show for the first time that main-chain organometallic polymers (MCOPs) can be prepared from Janus N-heterocyclic carbene (NHC) linkers and polynuclear cluster nodes. The crosslinked framework Co4 S4 -MCOP is synthesized via ligand displacement reactions and undergoes reversible electron transfer in the solid state. Discrete molecular cluster species can be excised from the framework by digesting the solid in solutions of excess monocarbene. Finally, we demonstrate a synthetic route to monodisperse framework particles via coordination modulation.